Magnesium Substitution in Ni‐Rich NMC Layered Cathodes for High‐Energy Lithium Ion Batteries (Adv. Energy Mater. 8/2022). Issue 8 (24th February 2022) - Gomez‐Martin, Aurora; Reissig, Friederike; Frankenstein, Lars; Heidbüchel, Marcel; Winter, Martin; Placke, Tobias; Schmuch, Richard
Abstract : Li‐Ion Batteries In article number 2103045, Aurora Gomez‐Martin, Richard Schmuch, and co‐workers report the effect of Mg substitution on mitigating the structural challenges of Ni‐rich layered oxide cathode materials upon cycling in lithium‐ion batteries. While partial substitution of Mg in Li sites linearly reduces the initial capacities at a given upper cut‐off cell voltage, the attainable cycle life is significantly extended.